An emerging market perspective of what makes professional service firms successful. Issue 1 (16th November 2020) - Sackey, Felix Nana Abaka; Caesar, Livingstone Divine
Abstract : Purpose: Despite the criticality of strategic partnerships to the survival and success of professional service firms (PSF) in emerging markets, there is a dearth of research on the subject matter. Specifically, not much is known concerning the dynamics of partnerships among small and medium-sized enterprises (SMEs) in the professional services sector of the economy. This paper aims to explore the dynamics of the impact of constructs such as attributes of partnership, communication behaviour and collaborative conflict resolution on partnership success. Design/methodology/approach: A quantitative survey sent to 300 small and medium-sized PSFs achieved a 79% response rate. The data is then analysed using bivariate and multi-variate techniques. Findings: The results revealed a positive relationship between two of the three constituents of attributes of the partnership (i.e. commitment and coordination) and the success of partnerships. Commitment and coordination emerged as the significant attributes of partners that affect the success of the partnership. Contrary to previous studies, trust and information sharing did not have a positive impact on partnership success. Practical implications: PSFs in emerging markets need concerted efforts to maintain competitive and sustainable partnerships. To make any significant impact, they must develop contemporary skills in collaborative conflict management. Originality/value: This paper highlights the need for PSFs and SMEs in other service sectors of emerging markets to harness partnerships as a valuable tool to overcome the policy shortcomings of current regulatory frameworks within their respective markets.